2016
DOI: 10.1016/j.jpge.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Self-Expandable Metal Stents for Colorectal Cancer: From Guidelines to Clinical Practice

Abstract: IntroductionColonic self-expandable metal stent placement is widely used for palliation of obstructive colorectal cancer. The European recommendations for stent placement as a bridge to elective surgery in obstructive colorectal cancer were recently reviewed. The aim of this study was to evaluate the efficacy and safety of stent placement in obstructive colorectal cancer and to discuss these recent guidelines.Materials and methodsDemographic characteristics, procedure indications, complications and final outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…SEMS placement has been applied over 20 years for the treatment of colonic obstruction[7]. As the stent type has evolved, colonic stents have been used to treat colonic malignancies either as a bridge to surgery or as a palliative measure[8,9]. As a bridge to surgery, the use of stents for potentially resectable colorectal cancers makes it possible to convert urgent to elective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…SEMS placement has been applied over 20 years for the treatment of colonic obstruction[7]. As the stent type has evolved, colonic stents have been used to treat colonic malignancies either as a bridge to surgery or as a palliative measure[8,9]. As a bridge to surgery, the use of stents for potentially resectable colorectal cancers makes it possible to convert urgent to elective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Single case series or series consisting of several cases have been reported in the literature. In a case series consisting of 36 cases, Costa Santos et al 14 reported that stenting was successfully performed in 2 cases with splenic flexura tumors. Similarly, stent application in cases with splenic flexura tumors was reported by Alcántara et al 15 in 6 patients, Arezzo et al 16 in 18 patients, Ho et al 17 in 4 patients, and Pirlet et al 18 in 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is the only procedure that allows for non-resectable jaundiced patients to be treated with neoadjuvant therapy [ 9 ], and a biopsy can be performed in the same intervention in order to reach a definitive diagnosis [ 10 ]. Furthermore, it allows for resectable patients to safely wait for surgical resection when it cannot be performed in a short-term period when they develop severe pruritus, severe hyperbilirubinemia, acute cholangitis, or jaundice-related systemic complications [ 11 , 12 ]. This procedure is not routinely recommended for patients taken in for surgical resection, as it can increase complications [ 5 ], and formal indications for its use are still debated [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that PBD is associated with a decrease in the rate of postoperative complications [ 8 , 13 ], while others have shown that this would be the same whether or not patients underwent PBD [ 11 , 14 , 15 ]. However, what seems to be the increasing consensus is that it leads to an increase in the rate of postoperative complications, especially infectious ones [ 9 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%